Variation and determinants of leaf anatomical traits from boreal to tropical forests in eastern China. (July 2022) - Ni, Xiaofeng; Sun, Lijuan; Cai, Qiong; Ma, Suhui; Feng, Yuhao; Sun, Yuanfeng; An, Lihua; Ji, Chengjun
Highlights: Leaf anatomical traits can reflect plants adaption to environmental changes. We measured leaf anatomical traits of 60 species in eight forests in eastern China. Leaf anatomical traits varied significantly among species, PFTs and biomes. The thickness of leaf tissues tended to increase from boreal to tropical forests. Spatial variations in leaf anatomical traits were mainly determined by the shifts in PFTs. Abstract: Leaf anatomical traits are responsive to environmental factors and thus highly plastic in their development and biochemical function. However, how they vary across large geographical scales and the main driving factors remain unclear, especially for forest plants. Here, by combining field sampling with plant semi-thin sectioning methods, eight anatomical traits (including leaf epidermis and mesophyll traits, leaf midrib and vascular traits) that can fully reflect leaf structure were measured in 60 plant species inhabiting eight forests in eastern China, and their geographical patterns and possible determinants were explored. Our results showed that leaf anatomical traits varied significantly among different plant functional types (PFTs), and phylogeny had a negligible effect on them. At the species level, leaf anatomical traits exhibited significant geographical patterns, and the thickness of leaf tissues tended to increase from boreal to tropical forests. Compared to leaf epidermis and mesophyll traits, leaf midrib and vascular traits showed similar and more significant geographical patterns. Moreover, the spatial variations in leaf anatomical traits were mainly determined by the shifts in PFTs, while climate and soil nutrient availability had relatively marginal effects. Our findings emphasized that leaf anatomical trait coordination could reflect the resource trade-off and utilization strategies of plants, which is expected to improve our understanding of the responses and adaptation mechanisms of plants to environmental changes.